“Personal @ Business” Businesses’/ Companies’ assets as matrimonial property; the legal policy / Zuhairah Ariff Abd Ghadas and Norliah Ibrahim - Abd Ghadas, Zuhairah Ariff; Ibrahim, Norliah (2010)
Matrimonial property disputes are one area of law, which is highly litigated before the registrars and judges. Under the Malaysian law, the court shall have power to order the division of any assets acquired by the divorced parties during the marriage including those attained by the sole efforts of one part to the marriage. Reference to personal property normally did not raise contentious issue as the court would apply the general rule / method in dividing or concluding the matrimonial property. However, when it comes to distribution of business assets or interest in business, particularly those which are under the business’s name, many legal issues may arise, such as rights or entitlement of the ex-spouse to claim, proportion and division of the assets as a matrimonial property and rights to future interest/benefits of the business assets/profits. This paper intends to look into policies/ approached of both the civil and Shariah courts in determining claims against the business’s or company’s assets as a matrimonial property. Research methodology which is adopted in this paper is statutory and doctrinal analysis.